A familial case of Galloway-Mowat syndrome due to a novel TP53RK mutation: a case report - Hye Sun Hyun; Seong Heon Kim; Eujin Park; Myung Hyun Cho; Hee Gyung Kang; Hyun Soon Lee; Noriko Miyake; Naomichi Matsumoto; Hiroyasu Tsukaguchi; Hae Il Cheong (BMC, 2018)
Abstract Background Galloway-Mowat syndrome (GAMOS) is a rare hereditary renal-neurological disease characterized by early-onset steroid-resistant nephrotic syndrome in combination with microcephaly and brain anomalies. Recently, novel causative mutations for this disease have been identified in the genes encoding the four KEOPS subunits: OSGEP, TP53RK, TPRKB, and LAGE3. Case presentation We detected a novel homozygous TP53RK mutation (NM_033550, c.194A > T, p.Lys65Met) using whole exome sequencing in a familial case of GAMOS with three affected siblings. All three patients manifested similar phenotypes, including very early-onset nephrotic syndrome (8 days, 1 day, and 1 day after birth, respectively), microcephaly, dysmorphic faces, and early fatality (10 months, 21 days, and 25 days of age, respectively). One patient also showed hiatal hernia with gastric volvulus. Renal biopsy performed on one patient revealed focal segmental glomerulosclerosis with severe tubulo-interstitial changes. Conclusion We report on a familial case of GAMOS with three affected siblings carrying a novel homozygous TP53RK mutation. To our knowledge, this is only the second report on GAMOS in association with a TP53RK mutation.